2022
DOI: 10.1111/ejn.15602
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting housing environment manipulation and acute loss of environmental enrichment impact BALB/c mice behaviour in multiple functional domains

Abstract: Understanding environmental influences on individuals' behaviour is challenging. Here we have investigated the housing impact of 9 weeks of enriched environment (EE) and social isolation (SI) and the impact of abrupt deprivation of EE (enrichment removal: ER) on BALB/c mice. Compared with the widely used C57BL/6 strain in research, BALB/c synthesises serotonin less efficiently due to a genetic variation and thus may potentially represent human populations at higher risk of stress‐related disorders. We assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…8,9 This enrichment-loss model corroborates previous findings that abrupt removal from an enriched environment was associated with rats' diminished motivation to explore in a radial arm maze. 10 Recently, enrichment disruption has been explored in mice noting increased aggression and social distancing, 11 as well as impaired cognition in mice exposed to both maternal immune activation and subsequent social isolation following long-term enriched environment exposure. 12 Numerous studies have confirmed that exposure to complex or enriched environments enhances neuroplasticity markers in laboratory animals 13,14 with evidence of individual differences 15,16 ; however, the pervasiveness and persistence of these effects, especially when animals are permanently relocated to more impoverished conditions, is a clinically relevant question deserving further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This enrichment-loss model corroborates previous findings that abrupt removal from an enriched environment was associated with rats' diminished motivation to explore in a radial arm maze. 10 Recently, enrichment disruption has been explored in mice noting increased aggression and social distancing, 11 as well as impaired cognition in mice exposed to both maternal immune activation and subsequent social isolation following long-term enriched environment exposure. 12 Numerous studies have confirmed that exposure to complex or enriched environments enhances neuroplasticity markers in laboratory animals 13,14 with evidence of individual differences 15,16 ; however, the pervasiveness and persistence of these effects, especially when animals are permanently relocated to more impoverished conditions, is a clinically relevant question deserving further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, our omics data indicate that ER does not simply reverse endpoints to SH levels, indicating that the latter does not represent a “baseline condition” to which the organism returns. Studies in mice indicate impairments in socially isolated controls, using adolescent BALB/c mice and a distinct removal protocol [ 54 ]. However, a similar study performed in Long-Evans rats yielded results more in-line with those seen here [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sukegawa and colleagues found that the removal of rodents from EE/EC elevated aggressive behaviors and disrupted sleeping patterns. The maladaptive behaviors were observed up to 2 weeks following enrichment removal [ 145 ].…”
Section: Plasticity-reducing Factorsmentioning
confidence: 99%